The incidence and aetiology of epistaxis in infants: a population-based study. Issue 6 (8th January 2009) - Paranjothy, S; Fone, David; Mann, M; Dunstan, F; Evans, E; Tomkinson, A; Sibert, J; Kemp, A
Abstract : Objective: To estimate the incidence and describe the aetiology of epistaxis in infants. Design: Population-based study including a retrospective hospital admission database analysis and a postal questionnaire to clinicians. Setting: Wales, United Kingdom. Methods: Cases of epistaxis over a 6-year period (1999–2004) were identified from the Patient Episode Dataset for Wales (PEDW) and validated using clinical information to calculate the population-based incidence and ascertain the causes of epistaxis in infants in Wales. Results: 36 confirmed cases were identified over the 6-year period giving an estimated annual incidence of epistaxis of 19.3 (95% CI 14.0 to 26.7) per 100 000 infants. The median age at admission was 12 weeks (interquartile range 4–33) (min 1 week, max 49 weeks). 23 of the infants had a recognised cause for their epistaxis (trauma (five), coagulation disorder (four), congenital anomaly (two), acute rhinitis or coryza (11), abusive smothering event (one)). No cause for the epistaxis was identified for 13 cases. Coagulation disorder was excluded in seven of these 13 infants but in the other six no attempt was made to exclude this disorder. Child abuse was suspected but excluded in four of the 13 cases. Conclusion: Hospital admission for epistaxis is a rare event. In the majority of cases in this study a simple explanation was available and proven physical abuse was rare. A bleeding disorder should always be considered and, if additional evidence suggests physical abuse, this must be excluded.